Regenerative Effects of Locally or Intra-Arterially Administered BMSCs on the Thin Endometrium - Guo, Qi; Chang, Yajie; Li, Jingjie; Zhou, Chuanchuan; Huang, Rui; Yang, Xing; Liu, Guihua; Liang, Xiaoyan (Frontiers in Bioengineering and Biotechnology, 2022)
Stem cell–based therapy plays a pivotal role in the regeneration of damaged endometrium. Previous studies have demonstrated the therapeutic potential of bone marrow mesenchymal stem cells (BMSCs) through diverse administration ways. However, the homing, survival, and differentiation potential of these differently administered BMSCs are poorly defined, and the best route of administration is not well-defined. Herein, we aim to compare the engraftment, retaining time, and therapeutic efficiency of differently administered BMSCs. To achieve this, GFP/Luc-labeled BMSCs administered in two modes were assessed in a thin endometrium rat model: either into the damaged horns directly or through the ipsilateral iliac artery. The retaining time and hemi-quantitative distribution were evaluated by in vivo bioluminescence imaging and immunohistological analysis. Locally administered BMSCs were strongly detected in the abdomen at the first 4 days post treatment but underwent a rapid decrease in luminescent signal afterward and were rarely found 28 days after treatment. In contrast, the retaining time of BMSCs injected through the iliac artery was longer, reflected by more GFP-positive cells detected in the uterine section 28 days post treatment. Differentiation toward endometrial stromal cells was observed. Both routes of administration contributed to the restoration of the damaged endometrium, showing a comparable increase in the endometrial thickness and a decrease in fibrosis. However, more importantly, higher expression of LIF and VEGF, better recruitment, and longer retainment were found in the intra-arterial administration, contributing to the establishment of the optimal administration mode in clinical practice.